High temperature tensile properties and deep drawing of fully green composites (eXPRESS Polymer Letters)
In recent years, research and development of materials using biomass sources are much expected to construct a sustainable society. The so-called green composite consisting of natural fibers and biodegradable resin, is one of the most promising materials in developing biomass products. In this study, especially, we focus on the tensile deformation behavior of the green composites reinforced with ramie woven fabrics at high temperature. The results show that the fracture strain at high temperatures increases larger than that of room temperature, and initial deformation resistance of the composites seen at room temperature does not appear at high temperatures. Thus, several conditions to cause more deformability of the green composites were found. Finally, in order to utilize such deformability, Lankford-values of the green composites were clarified, and deep drawing was carried out for sheet materials made of the green composites.